Students and Educational Productivity - Levin, Benjamin (Education Policy Analysis Archives, 1993)
The literature on productivity in education is extensive. The object of this effort is to find a production function–a mathematical expression of the relationship between inputs and outputs in education. In this paper, the status of the literature on production functions is reviewed. Most of these approaches have seen schooling as something that is done to students, rather than thinking about education as something that students essentially do for themselves. An argument is developed that makes students the key factors in shaping school outcomes, and therefore a central focus of our thinking about productivity. The paper concludes with suggestions for research and policy.